A One-Dimensional Pt Degradation Model for Polymer Electrolyte Fuel Cells. Issue 8 (7th May 2015) - Li, Yubai; Moriyama, Koji; Gu, Wenbin; Arisetty, Srikanth; Wang, C. Y.
Abstract : A one-dimensional model is developed and validated to study platinum degradation and the subsequent electrochemical surface area (ECA) loss in the cathode catalyst layer (CL) of polymer electrolyte fuel cells (PEFCs). The model includes two mechanisms of Pt degradation: Ostwald ripening on carbon support and Pt dissolution-re-precipitation through the ionomer phase. Impact of H2 | N2 or H2 | Air operation, operating temperature, and relative humidity (RH) on Pt degradation during voltage cycling is explored. It is shown that ECA loss is non-uniform across the cathode CL with a zone of exacerbated Pt degradation and hence much lower ECA found near the membrane. This non-uniform Pt degradation is caused by consumption of Pt ions by crossover H2 in both H2 | N2 and H2 | Air systems. An important consequence is that thinning the cathode electrode in a fuel cell would lead to more ECA loss as a higher fraction of the thin CL would fall in this exacerbated degradation zone. We have quantified the effect of thin cathode CLs on Pt degradation for the first time.